The Dynamics of Rainfall and Humidity in Dengue Fever Epidemiology: A Case Study of Surakarta City - Nurhasan Agung Prabowo; Tonang Dwi Ardyanto; Risalina Myrtha; Hendrastutik Apriningsih; Frieska Dyanneza; Niken Dyah Aryani Kuncorowati; Adji Suwandono; Laily Shofiyah; Maria Galuh Kamenyangan Sari; Novianto Adi Nugroho (Poltanesa, 2025)
Dengue Fever is a significant and recurring public health challenge in tropical urban centers, including the city of Surakarta, Indonesia. The transmission of this vector-borne disease is highly sensitive to local climatic conditions, as high rainfall and humidity create ideal environments for the proliferation of the Aedes aegypti mosquito. This study aims to analyze the epidemiological trends of Dengue Fever in Surakarta from 2021 to 2023 and to determine the influence of key environmental factors on disease transmission dynamics. A descriptive epidemiological study was conducted using secondary data on reported Dengue Fever cases across Surakarta's five sub-districts: Laweyan, Serengan, Pasar Kliwon, Jebres, and Banjarsari. Incidence rates per 100,000 population were calculated and correlated with monthly rainfall and humidity data. The results showed significant fluctuations in incidence, with a major surge in 2022, when 166 total cases were recorded. The district of Laweyan recorded the highest incidence rate that year at 134.59 cases per 100,000 population. This peak strongly correlated with high rainfall and humidity during the first quarter of 2022, which provided optimal mosquito breeding conditions. In contrast, 2021 had the lowest incidence amid drier conditions. These findings confirm a strong association between climatic factors and Dengue Fever transmission in Surakarta. High rainfall and humidity are critical contributors to the disease burden, underscoring the urgent need for integrated, climate-based forecasting within public health surveillance systems to mitigate future outbreaks effectively.